Synthesis of Functionalized 2‐(4‐Hydroxyphenyl)‐3‐methylbenzofuran Allosteric Modulators of Hsp90 Activity. Issue 20 (17th June 2016) - Sattin, Sara; Panza, Matteo; Vasile, Francesca; Berni, Francesca; Goti, Giulio; Tao, Jiahui; Moroni, Elisabetta; Agard, David; Colombo, Giorgio; Bernardi, Anna
Abstract : Hsp90 is a molecular chaperone that plays a pivotal role in the cell life cycle. ATP‐regulated internal dynamics are critical to Hsp90 function and we recently demonstrated that these dynamics can be modulated in an allosteric fashion; the protein C‐terminal domain (CTD) can be effectively targeted with a family of 2‐phenyl‐benzofuran derivatives. Here we describe the expansion of the initial library, reporting 28 new derivatives that explore the chemical space at opposite ends of the benzofuran scaffold. Interactions of the compounds with a full‐length protein homolog were explored by Saturation Transfer Difference (STD) NMR spectroscopy. In this context we also report the interaction epitope of Novobiocin, a known CTD inhibitor. Abstract : Hsp90 ATP‐regulated internal dynamics can be modulated in an allosteric fashion, targeting the protein C‐terminal domain (CTD) with a family of 2‐phenylbenzofuran derivatives. Here we report 28 new derivatives that explore chemical space at opposite ends of the benzofuran scaffold. Compound interactions with Hsc82, a yeast isoform of full‐length Hsp90, were explored using STD‐NMR spectroscopy.